2015
DOI: 10.1080/09540121.2015.1026307
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of HIV-infected adolescents enrolled in a disclosure intervention trial in western Kenya

Abstract: Knowledge of one’s own HIV status is essential for long-term disease management, but there are few data on how disclosure of HIV status to infected children and adolescents in sub-Saharan Africa is associated with clinical and psychosocial health outcomes. We conducted a detailed baseline assessment of the disclosure status, medication adherence, HIV stigma, depression, emotional and behavioral difficulties, and quality of life among a cohort of Kenyan children enrolled in an intervention study to promote disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 45 publications
4
67
0
Order By: Relevance
“…The commonest immediate emotional impacts of the disclosure were depression, sadness and shock. This was in keeping with the fears of the caregivers in delaying disclosure [21,22] and findings from other studies [16,23,24]. Namukwaya, et al [25] observed that disclosure of HIV status to children led to them being terrified, worried, confused, and intensely emotional.…”
Section: Fig 2 Major Concerns About Being Hiv-infectedsupporting
confidence: 83%
“…The commonest immediate emotional impacts of the disclosure were depression, sadness and shock. This was in keeping with the fears of the caregivers in delaying disclosure [21,22] and findings from other studies [16,23,24]. Namukwaya, et al [25] observed that disclosure of HIV status to children led to them being terrified, worried, confused, and intensely emotional.…”
Section: Fig 2 Major Concerns About Being Hiv-infectedsupporting
confidence: 83%
“…In addition, external events, such as enrollment in school (25, 33) or admission to the hospital (35, 36, 40), were cited as motivating disclosure.…”
Section: Discussionmentioning
confidence: 99%
“…At least one study, interviewing children, reported that disclosure was not associated with more negative psychological outcomes (40). Knowing one’s HIV status does appear to be associated with stable or improved child well-being (18, 48) and disease management (1113).…”
Section: Discussionmentioning
confidence: 99%
“…The retained variables were again assessed for internal consistency using Cronbach's Alpha to ascertain that the internal consistency for each domain improved. Furthermore, the retained variables in each domain were summed up and scaled so as to derive a score ranging from 0 to100 using the following formula [32].…”
Section: Data Collection and Analysismentioning
confidence: 99%